Um modelo baseado em autômatos celulares e algoritmos genéticos para a navegação de um time de robôs visando o controle de formação e o desvio de obstáculos - Silva, Reslley Gabriel Oliveira (2015)
Formation control is the task of coordinating a group of robots to get into and to maintain a formation with a specific shape while moving in the environment. In this work we investigated models based on cellular automata applied to this problem. We implemented methods previously proposed in the literature and found some key limitations that worsened the robot s trajectory quality. Thus, we created an evolutionary-cooperative method, using the convergence and dynamics of a genetic algorithm along with the compact rules and simplified processing of cellular automatas. The new method required low computational infrastructure and was tested both in simulation and in real world experiments. At the end, the new model exhibited better behaviours than their precursors in several scenarios, improving the robot s trajectory and formation maintenance.